Analisis Kelayakan Proyek Investasi Layanan Spa: Studi pada Perusahaan PT. Bias Puspa Kreasi - Ningrat, Giovanni Andi; Kountur, Ronny (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
This study uses a feasibility study in investment decisions on several choices of PT. Bias Puspa Kreasi.This study aims to determine the company cash flow projection in the analysis income expenditure report in 5 years and determine which investments provide the maximum profit. The data sources in this study are divided into primary and secondary data to obtain internal database reports in the form of financial reports. The method used is through the approach of financial and non-financial aspects in calculating the feasibility of a project (financial decision). The analysis shows that the D hotel, namely Swiss Bell Balikpapan, provides a Net Present Value of a positive Internal Rate of Return that exceeds the specified discount rate, the Profitability index exceeds the average, and the Payback Period is the shortest. Furthermore, sensitivity analysis shows that investment in Spa services tends to be sensitive to the percentage of hotel visitors converted into Spa service users (customer acquired) and the growth of Spa service users (growth projection). The recommendations for further business development are in the form of a more efficient and effective reporting and recording system for the company.